Effects of Technological Equipment at Home on School Readiness of 5-6-Year-Old Children - (:unkn) unknown (WYDAWNICTWO ADAM MARSZALEK, 2011)
This study was conducted to evaluate the effects of technological equipment at home on school readiness of primary school children. The sample of the study consisted of 300 children at the ages of 5, 5.5, and 6. The data were gathered through a survey form which consisted of 6 questions and Development and Implementation forms of the Marmara Scale for Primary School Readiness. The results were analyzed using t test and analysis of variance with one dimension. The results indicated that a number of variables related to technological equipment at home of pre-school children led to differences in primary school readiness. For this reason, educating parents and teachers about improving the conditions of home environment in terms of technological equipment and preparing programs in order to support parents economically to provide technological equipment for their children is of importance in relation to primary school readiness.
Keywords: school readiness; technological equipment; pre-school children